The Nature whence Spirit came: on Adrian Johnston’s Hegelianism - TupinambáGabriel (Stasis, 2016)
Book review: Adrian Johnston, Prolegomena to Any Future Materialism. Vol. I. The Outcome of Contemporary French Philosophy Evanston, IL: Northwestern University Press, 2013, 257pp., ISBN 978-0810129122 Adrian Johnston, Adventures in Transcendental Materialism. Dialogues with Contemporary Thinkers Edinburgh: Edinburgh University Press, 2014, 376pp., ISBN 978-0748673285